2019
DOI: 10.1055/s-0038-1676768
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation in Sporadic Vestibular Schwannoma: A Systematic Literature Review

Abstract: Objective This study was aimed to perform a systematic literature review by examining outcomes in patients with sporadic vestibular schwannoma (VS) undergoing ipsilateral cochlear implant (CI). Data Sources PubMed-NCBI (National Center for Biotechnology Information) and Scopus databases were searched through October 2017. Study Selection Studies reporting auditory outcomes for each patient when a CI was placed with an ipsilateral sporadic VS were included. Main Outcome Measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 50 publications
0
44
2
3
Order By: Relevance
“…Through transcranial direct bone conduction to the contralateral cochlea, BAHAs eliminate the head shadow and enable patients to hear and communicate on the deaf side. These devices have been proven to restore some binaural hearing, thus improving the patients' QoL [9]. While providing no benefit for sound localization, BAHAs improve speech discrimination in noisy surroundings, thereby diminishing the social, physical, and psychological stress.…”
Section: Unilateral Hearing Lossmentioning
confidence: 99%
See 3 more Smart Citations
“…Through transcranial direct bone conduction to the contralateral cochlea, BAHAs eliminate the head shadow and enable patients to hear and communicate on the deaf side. These devices have been proven to restore some binaural hearing, thus improving the patients' QoL [9]. While providing no benefit for sound localization, BAHAs improve speech discrimination in noisy surroundings, thereby diminishing the social, physical, and psychological stress.…”
Section: Unilateral Hearing Lossmentioning
confidence: 99%
“…While providing no benefit for sound localization, BAHAs improve speech discrimination in noisy surroundings, thereby diminishing the social, physical, and psychological stress. A systematic review on functional outcomes after cochlear implant (CIs) in patients with sporadic VSs reported a 30 to 56.4% improvement in mean speech discrimination score and an improvement in tinnitus [9]. Although the use of follow-up MRIs in patients with CIs is considered to be limited due to imaging artifacts [9], Carlson et al [22] showed that under controlled conditions, 1.5-T MRI can successfully evaluate the ipsilateral skull base.…”
Section: Unilateral Hearing Lossmentioning
confidence: 99%
See 2 more Smart Citations
“…Die American Academy of Otolaryngology -Head and Neck Surgery (AAO-HNO) schlägt 4 Klassen (A-D) vor [1], wohingegen die Klassifikation nach Gardner und Robertson [10] 5 Klassen [1][2][3][4][5] unterscheidet und auf die Silverstein-Klassifikation (Klassen I-V) zurückgeht [35]. Im deutschsprachigen Raum wurde die "New-Hannover-Klassifikation" mit 5 Stufen (H1-H5) entwickelt [29].…”
Section: Hörklassen Bei Patienten Mit Vestibularisschwannom Bei Verweunclassified